PENGARUH MULTIMEDIA ARTICULATE STORYLINE TERHADAP KETERAMPILAN BERCERITA MATERI FOLKLORE SISWA SD NEGERI 060937 KWALA BEKALA - Sidebang, Restio; Karo, Karmila Br (Universitas Quality, 2024)
This research aims to determine students' storytelling skills using multimedia Articulate Storyline for class IV students and to determine the significant effect of using multimedia Articulate Storyline for class VI students at SDN 060937 Kwala Bekala. The research method is quantitative. The type of research applied is quasi-experimental (one group pretest posttest design). The research sample was all class VIB students at SDN 060937 Kwala Bekala. Based on the results of research in the experimental class, the average posttest score was 81. Based on statistical calculations of independent tests between two factors for class VI-B experimental class, there was a significant influence in the use of Articulate Storyline multimedia on students' storytelling skills in the Indonesian language subject material. folklore in class VI of SD Negeri 060937 Kwala Bekala T.P 2023/2024, the researcher obtained the result that there was a significant influence with the results of the independent test between the two factors (B x K) used, so that the experimental class post test data obtained x^2 data. ≥ x^2 (1- ∝)(B-1)(K-1) is expressed as 23.88 ≤ 68.058. Conclusions from the research, the hypothesis is acceptable and there is an influence of the use of Multimedia Articulate Storyline on elementary school students' Folklore Storytelling Skills.